2015
DOI: 10.5194/gmd-8-317-2015
|View full text |Cite
|
Sign up to set email alerts
|

ASAM v2.7: a compressible atmospheric model with a Cartesian cut cell approach

Abstract: Abstract. In this work, the fully compressible, threedimensional, nonhydrostatic atmospheric model called All Scale Atmospheric Model (ASAM) is presented. A cut cell approach is used to include obstacles and orography into the Cartesian grid. Discretization is realized by a mixture of finite differences and finite volumes and a state limiting is applied. Necessary shifting and interpolation techniques are outlined. The method can be generalized to any other orthogonal grids, e.g., a lat-long grid. A linear imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…This study showed that a flat island with the characteristics of the Santiago Island (Cabo Verde) can induce the generation of gravity waves and enhance the aerosol downward mixing, only through its heat island effect, without taking into account its orography. Another recent LES study (Jähn et al, 2016) conducted in the Barbados area also revealed the presence of island induced gravity waves on the lee side of the island and provided further insight into the dust turbulent downward mixing, cloud generation and boundary layer modification in the lee side of the island. In contrast with the previous case, the heating effect and the orography were taken into account in this case.…”
Section: F Chouza Et Al: Vertical Wind Retrieved By Airborne Lidar mentioning
confidence: 78%
“…This study showed that a flat island with the characteristics of the Santiago Island (Cabo Verde) can induce the generation of gravity waves and enhance the aerosol downward mixing, only through its heat island effect, without taking into account its orography. Another recent LES study (Jähn et al, 2016) conducted in the Barbados area also revealed the presence of island induced gravity waves on the lee side of the island and provided further insight into the dust turbulent downward mixing, cloud generation and boundary layer modification in the lee side of the island. In contrast with the previous case, the heating effect and the orography were taken into account in this case.…”
Section: F Chouza Et Al: Vertical Wind Retrieved By Airborne Lidar mentioning
confidence: 78%
“…The soil class "loam" was chosen to represent the average island soil type. Hydraulic and thermal parameters of this soil type can be found in Doms et al (2011) and Jähn et al (2015). For land surface parameterization, "shrubland" appears to be a good compromise between coastal beach areas and forest in the island interior.…”
Section: Forcingsmentioning
confidence: 99%
“…An extensive model description is presented in Jähn et al (2015), both covering numerical discretization methods and physical parameterizations. A special feature of ASAM is the usage of so-called cut cells for the orography.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations associated with the MelCol 2015 measurement campaign are performed with the All Scale Atmospheric Model (ASAM, Jähn et al, 2015). It has recently been used to investigate heat island effects on atmospheric boundary layer modification, cloud initiation and vertical tracer mixing in the trade wind regime (Jähn et al, 2016).…”
mentioning
confidence: 99%